PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POP UP BOOK TERHADAP KECERDASAN LINGUISTIK: PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POP UP BOOK TERHADAP KECERDASAN LINGUISTIK - Rizki Puji Astuti (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
This study aims to determine the effect of thelearning model Contextual Teaching and Learning (CTL) assisted bymedia pop up book on linguistic intelligence in fourth grade students at SDN Ngargogondo, Borobudur District, Magelang Regency. This study uses an experimental research type with aresearch design pre-experimental Design with the